PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF BERBASIS INKUIRI TERBIMBING PADA MATERI ZAT ADIKTIF KELAS VIII SMP/MTS - Syafira, Rahmi Putri (rc-institut, 2019)
In the 2013 curriculum requires learning active students looking for or finding their own concepts not just reading and memorizing every concept that exists.The scientific approach in accordance with the 2013 curriculum is one of them guided inquiry learning models. Addictive substances is the science subject matter for grade VIII SMP in semester one. addictive substances can not be practiced and demonstrated because the material to be used may not be carried carelessly. To understand this material we need a media that are suitable with curriculum 2013. The purpose of this research was to develop powerpoint interactive learning media based on guided inquiry on addictive material and showed the validity and practicality. The type of reseach used to get product is reseach and development (R&D) with 4-D models. Powerpoint interactive validity testing is carried out by 3 chemistry lecturers at FMIPA UNP and 2 natural science teacher at SMP Pembangunan Laboratorium UNP. The practicality questionnaire was failled by 2 natural science teacher and 20 student in grade IX at SMP Pembangunan Laboratorium UNP. Data from the validity and practicality results were analyzed using the cohen Kappa formula. From the results of the validity, the average of kappa moment was 0.84 with a very high validity category. From the results of the practicality on the teacher, the average of kappa moment was 0.89 and the students were 0.88 with a very high practicality category.base on the result, the resulting interactive powerpoint is valid and practical.